2022
DOI: 10.4103/abr.abr_366_21
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Magnesium in Insulin Secretion and Insulin Resistance

Abstract: Insulin resistance (IR) is a chronic pathological condition that is related to reduce the rates of glucose uptake, especially in the liver, muscle, and adipose tissue as target tissues. Metabolic syndrome and type 2 diabetes mellitus can occur following progression of the disease. The majority of prior research has applied that some cations such as magnesium (Mg2+) have important physiological role in insulin metabolism. Mg2+ is the fourth most abundant mineral in the human body that gets involved as a cofacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…24 Mg supplementation could increase insulin secretion and improve the ability of beta-cells to compensate for changes in insulin sensitivity in healthy individuals. 25 Mg intake has also been strongly and negatively correlated with metabolic syndromes. Hypomagnesemia has been independently associated with the development of IGT.…”
Section: Discussionmentioning
confidence: 99%
“…24 Mg supplementation could increase insulin secretion and improve the ability of beta-cells to compensate for changes in insulin sensitivity in healthy individuals. 25 Mg intake has also been strongly and negatively correlated with metabolic syndromes. Hypomagnesemia has been independently associated with the development of IGT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high daily magnesium consumption can reduce the risk of developing type 2 diabetes [22]. A meta-analysis of numerous studies showed that the oral consumption of magnesium supplements and the incorporation of the right foods into one's diet can significantly enhance insulin sensitivity and metabolic control in people with type 2 diabetes [23]. The strong correlation between hypomagnesemia and diabetes is further elaborated upon in Figure 1.…”
Section: Hypomagnesemia and Diabetesmentioning
confidence: 96%